2019
DOI: 10.1007/s13346-019-00675-6
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles attenuate albuminuria by inhibiting podocyte injury in a rat model of diabetic nephropathy

Abstract: Several recent studies have reported that gold nanoparticles (AuNPs) attenuate hyperglycemia in diabetic animal models without any observed side effects. The present study was intended to provide insight into the effects of 50nm AuNPs on diabetic kidney disease. Adult male rats were divided into three groups (n = 7/group): control (nondiabetic, ND), diabetic (D), and diabetic treated intraperitoneally with 50-nm AuNPs (AuNPs + D; 2.5 mg/kg/day) for 7 weeks. Diabetes was induced by a single-dose injection of 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…AuNPs demonstrated antioxidant effects via quenching reactive oxygen species (ROS), such as superoxide anion radical (O 2 − ) and H 2 O 2 in a dose-dependent manner [27,30]. Other studies have also revealed anti-hyperglycemic, anti-inflammatory, and antioxidative activities of AUNPs in diabetic animals [24,31], collagen-induced arthritis [32], and bone loss models [33].…”
Section: Introductionmentioning
confidence: 99%
“…AuNPs demonstrated antioxidant effects via quenching reactive oxygen species (ROS), such as superoxide anion radical (O 2 − ) and H 2 O 2 in a dose-dependent manner [27,30]. Other studies have also revealed anti-hyperglycemic, anti-inflammatory, and antioxidative activities of AUNPs in diabetic animals [24,31], collagen-induced arthritis [32], and bone loss models [33].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that gold NPs (AuNPs) attenuate hyperglycemia in diabetic animal models without any observed side effects. Our research showed that AuNPs treatment prevented diabetes-associated increases in the BGL via the downregulation effect of AuNPs in renal mRNA or the protein expression of transforming growth factor β1 (TGF-β1), collagen IV, fibronectin, vascular endothelial growth factor-A (VEGF-A), and TNF-α [103]. In another study, the anti-hyperglycemic activity of AuNPs in STZ-induced diabetic animal models has been estimated.…”
Section: Contribution Of Authors To the Nano-based Diabetes Therapymentioning
confidence: 68%
“…The nephrin is essential for normal glomerular function. Preservation and permeability of the glomerular filtration barrier integrity is associated with the presence of proteins such as nephrin and podocin 22 .…”
Section: Discussionmentioning
confidence: 99%